Serpentinization of mantle‐derived peridotites at mid‐ocean ridges: Mesh texture development in the context of tectonic exhumation - Stéphane Rouméjon; Mathilde Cannat (Geochemistry, Geophysics, Geosystems)
Abstract At slow spreading ridges, axial detachment faults exhume mantle‐derived peridotites and hydrothermal alteration causes serpentinization in a domain extending more than 1 km next to the fault. At the microscopic scale, serpentinization progresses from a microfracture network toward the center of olivine relicts and forms a mesh texture. We present a petrographic study (SEM, EBSD, and Raman) of the serpentine mesh texture in a set of 278 abyssal serpentinized peridotites from the Mid‐Atlantic and Southwest Indian Ridges. We show that serpentinization initiated along two intersecting sets of microfractures that have consistent orientations at the sample scale, and in at least one studied location, at the 100 m scale. We propose that these microfractures formed in fresh peridotites due to combined thermal and tectonic stresses and subsequently served as channels for serpentinizing fluids. Additional reaction‐induced cracks developed for serpentinization extents <20%. The resulting microfracture network has a typical spacing of ∼60 µm but most serpentinization occurs next to a subset of these microfractures that define mesh cells 100–400 µm in size. Apparent mesh rim thickness is on average 33 ± 19 µm corresponding to serpentinization extents of 70–80%. Published laboratory experiments suggest that mesh rims formation could be completed in a few years (i.e., quasi instantaneous at the plate tectonic timescale). The depth and extent of the serpentinization domain in the detachment fault's footwall are probably variable in time and space and as a result we expect that the serpentine mesh texture at slow spreading ridges forms at variable rates with a spatially heterogeneous distribution.